An Atmospheric Pressure Chemical Ionization MS/MS Assay Using Online Extraction for the Analysis of 11 Cannabinoids and Metabolites in Human Plasma and Urine. Issue 5 (October 2017) - Klawitter, Jelena; Sempio, Cristina; Mörlein, Sophie; De Bloois, Erik; Klepacki, Jacek; Henthorn, Thomas; Leehey, Maureen A.; Hoffenberg, Edward J.; Knupp, Kelly; Wang, George S.; Hopfer, Christian; Kinney, Greg; et al.
Abstract : Background: Although, especially in the United States, there has been a recent surge of legalized cannabis for either recreational or medicinal purposes, surprisingly little is known about clinical dose–response relationships, pharmacodynamic and toxicodynamic effects of cannabinoids such as Δ9-tetrahydrocannabinol (THC). Even less is known about other active cannabinoids. Methods: To address this knowledge gap, an online extraction, high-performance liquid chromatography coupled with tandem mass spectrometry method for simultaneous quantification of 11 cannabinoids and metabolites including THC, 11-hydroxy-Δ9-tetrahydrocannabinol, 11-nor-Δ9-tetrahydrocannabinol-9-carboxylic acid, 11-nor-Δ9-tetrahydrocannabinol-9-carboxylic acid glucuronide (THC-C-gluc), cannabinol, cannabidiol, cannabigerol, cannabidivarin, Δ9-tetrahydrocannabivarin (THCV), and 11-nor-9-carboxy-Δ9-tetrahydrocannabivarin (THCV-COOH) was developed and validated in human urine and plasma. Results: In contrast to atmospheric pressure chemical ionization, electrospray ionization was associated with extensive ion suppression in plasma and urine samples. Thus, the atmospheric pressure chemical ionization assay was validated showing a lower limit of quantification ranging from 0.39 to 3.91 ng/mL depending on study compound and matrix. The upper limit of quantification was 400 ng/mL except for THC-C-gluc with an upper limit of quantification of 2000 ng/mL. The linearity was r > 0.99 for all analyzed calibration curves. Acceptance criteria for intrabatch and interbatch accuracy (85%–115%) and imprecision (<15%) were met for all compounds. In plasma, the only exceptions were THCV (75.3%–121.2% interbatch accuracy) and cannabidivarin (interbatch imprecision, 15.7%–17.2%). In urine, THCV did not meet predefined acceptance criteria for intrabatch accuracy. Conclusions: This assay allows for monitoring not only THC and its major metabolites but also major cannabinoids that are of interest for marijuana research and clinical practice. Abstract : Supplemental Digital Content is Available in the Text.